How Distributors’ Service Quality Drove Revisit Intention: Evidence Of Music Conventions And Exhibitions - Annas, Mohammad; Humairoh, Humairoh (Dinasti Publisher, 2024)
The study aimed to analyze relationship factors affecting revisit intention in music industries in particular music industries in major cities of Indonesia. The substance variables were core service quality and peripheral service quality. The intermediary variables involved were appraisal emotion and perceived value. Structural equation model analysis was developed involving more than dozens of music event organizers in major cities of Indonesia. The results of this study showed that the data supports the phenomenon and the literature that had been built. Appraisal emotion had a positive influence on perceived value. The results of this study showed that the data supports the phenomenon and the literature that had been built. This proved that the sense of pleasure that arises from good customer service and music performances, as well as music performances that could fulfill a person's emotional desires and needs for music festivals, were able to create value felt by visitors to the music festival itself. Core service quality had a positive influence on appraisal emotion with a t-value of 1.85.